Influence of Stent Length on Peri-Procedural Myocardial Injury after Percutaneous Coronary Intervention (Cardiovascular Journal, 2014)
Background: About one-third of all elective PCI procedures are associated with significant myocardial injury termed peri-procedural myocardial injury (PMI), which has been associated with increased subsequent mortality. The stent length is one of the factors that can predict procedure related Troponon I release. Methods: This interventional study was carried out to evaluate the influence of stent length on peri procedural myocardial injury by measuring post procedural release of Troponin I after percutaneous coronary intervention. Patients with e70% stenosed single vessel disease undergoing percutaneous coronary intervention with single stent were considered. Exclusion criteria were pre-procedural elevation of cardiac Troponin I above the 99th percentile of upper reference, severely ill patients. Total 90 consecutive patients were included. Among them 45 patients had d 20mm long stent (group A) and rest 45 patients had > 20mm long stent (group B). Blood samples for Troponin I were collected before procedure and 12 hours after procedure. Results: Baseline characteristics including age, sex, risk factor for ischaemic heart disease and clinical diagnoses were almost similar between the two groups. During procedure no complications concurred 93.3% patients in group A and 68.9% patients in group B (p